Structural Racism In Angie Thomas's Novel The Hate U Give (2017) - Geovani De silva Ananda; Muhd. Al Hafizh (Universitas Negeri Padang, 2020)
This article discusses a novel entitled The Hate U Give (2017) by Angie Thomas. The issue raises structured racism against African-Americans after the existence of human rights and to find out to what extent the implied author contributed to expressing the issue. This analysis uses Gramsci's Hegemony theory, interpretation of the text and context to dissect the contents of the novel. The results of the analysis shows that structured racism can be seen in two forms: the media and institutions. First of the two is the media as a stereotype circulator and the last of the two the institution discriminates against African-Americans.